Dysregulation of the 3β-hydroxysteroid dehydrogenase type 2 enzyme and steroid hormone biosynthesis in chronic kidney disease - Zuo, Yiyi; Zha, Dongqing; Zhang, Yue; Yang, Wan; Jiang, Jie; Wang, Kangning; Zhang, Runze; Chen, Ziyi; He, Qing (Frontiers in Endocrinology, 2024)
Chronic kidney disease (CKD) presents a critical global health challenge, marked by the progressive decline of renal function. This study explores the role of the 3β-hydroxysteroid dehydrogenase type 2 enzyme (HSD3B2) and steroid hormone biosynthesis pathway in CKD pathogenesis and progression. Using an adenine-induced CKD mouse model, we conducted an untargeted metabolomic analysis of plasma samples to identify key metabolite alterations associated with CKD. Metabolic characteristics revealed significant metabolic shifts in CKD, with 61 metabolites increased and 65 metabolites decreased, highlighting the disruption in steroid hormone biosynthesis pathways influenced by HSD3B2. A detailed examination of seven key metabolites underscored the enzyme's central role. Further supported by Nephroseq and Human Protein Atlas data, HSD3B2 exhibited a strong correlation with kidney function. A drastic reduction in its expression in CKD-affected kidneys was confirmed through immunohistochemistry, Western blotting, and qPCR analyses in both human and mouse tissues.Suppressed proliferation and increased apoptosis rate in HSD3B2 knocked down HK2 cells further demonstrated its significance in regulating renal pathophysiology. These findings underscore the potential of HSD3B2 as a clinical diagnostic and therapeutic target in CKD.While further studies are warranted to elucidate the mechanisms fully, our results provide valuable insights into the intricate interplay between steroid hormone biosynthesis and CKD, offering a promising avenue for precision medicine approaches and personalized treatment strategies.